Effects of different drying techniques on sea buckthorn pomace: comprehensive assessment of drying characteristics, physicochemical properties, and odor - Zhou, Xiang; Zhang, Xiaoqiang; Liu, Xinyu; Ji, Xinyu; Zhang, Qian; Yang, Xuhai (Frontiers in Sustainable Food Systems, 2024)
This study investigated the effects of hot air drying (HAD), infrared-assisted hot air drying (IR-HAD), vacuum freeze drying (VFD), and pulsed-vacuum drying (PVD) on the drying characteristics, color, microstructure, total phenolic content (TPC), total flavonoid content (TFC), vitamin C (Vc) content, and the odor analysis using electronic nose of sea buckthorn pomace. The results showed that IR-HAD exhibited the highest drying rate and the shortest drying time (250min). PVD exhibited the highest TPC, TFC, and Vc content while maintaining a color difference ΔE value closest to that of the fresh sample. PVD microstructure exhibited no collapse, fewer pores, and smaller cracks than the IR-HAD and VFD microstructures. Furthermore, the PVD pomace displayed the lowest reactivity to sulfides and ethanol compounds. The comprehensive analysis suggests that PVD holds promise as a drying method for sea buckthorn pomace and provides valuable insights for selecting an appropriate drying method for sea buckthorn pomace.